Corporate Social Responsibility Practices of Selected Airline Companies: Inputs for a Sustainable Aviation Service - Areola, PhD HSG, Eunice Mareth Querol; Amurao, Gomeriano Vallecer (Journal of Sustainable Community Development (JSCD), 2024)
This paper tries to identify the strategic corporate social responsibility of selected airline companies to ascertain inputs for the creation of a sustainable service delivery, by looking at the implementation level of its corporate social responsibility in the environmental, philanthropic, economic and ethical areas. The study shows that in terms of environmental responsibility, waste segregation has the highest level of practice, while carbon footprint reduction is the lowest. Philanthropic activities participated in by employees is the most frequently practiced among other philanthropic responsibility initiatives, while the provision of scholarship grants is the least practiced. For economic responsibility, the recruitment of diverse talent received the highest mean score indicating it as the most practiced activity, while financial management strategy practices is the most challenged. As far as ethical responsibility is concerned, the practice of honesty is prevalent, while direct stakeholder involvement in planning the manual of ethical operations is almost none. The study also explored whether there was a significant difference in the assessment of CSR strategies between the two groups of respondents. The results indicated that there was a significant difference in the assessments of employees and passengers in terms of environmental, philanthropic, economic, and ethical responsibilities in comparison to management administrators. Moreover, the challenges encountered in the implementation of CSR strategies were identified and ranked, providing insights into the perceived difficulties faced by airline companies in implementing CSR strategies. Based on the findings of the study, recommendations for responding to the challenges of implementing CSR strategies were proposed. These recommendations include additional signage for environmental awareness, ensuring the sustainability of philanthropic activities, crafting financial measures to address constraints, and ensuring sustainable implementation of its manual of operation. The findings and recommendations provides inputs to for a sustainable service delivery and promoting responsible business practices in the airline industry.